Transient Hot-Wire Experimental System for Measuring the Effective Thermal Conductivity of a Ceramic Breeder Pebble Bed. (3rd October 2017) - Kang, Christopher; Park, Yi-Hyun; Van Lew, Jon T.; Ying, Alice; Abdou, Mohamed; Cho, Seungyon
Abstract: Characterizing the thermo-physical properties of the ceramic breeder pebble bed is an integral step of developing breeder blankets for fusion energy applications. To that end, thermal conductivity is an important parameter to identify. In granular pebble bed materials, the thermal conductivity depends on the solid pebble material as well as any gas filling the interstitial void spaces, thus an effective thermal conductivity ( ) of the bulk is used. A transient hot-wire apparatus is developed through a collaborative study between the Fusion Science and Technology Center at UCLA and the National Fusion Research Institute (NFRI) to measure the effective thermal conductivity of Korean-made Li2 TiO3 pebble beds. In this study, current is pushed through a single strand of high purity platinum wire. The heat generated is conducted away by the surrounding pebble bed; the logarithmic change in temperature being used to calculate the rate of heat conductance. The apparatus is filled with roughly an atmosphere of helium and placed in a furnace to test the pebble bed under reactor relevant temperatures. Results and future improvements are presented.